Pencucian Uang dan Kejahatan Terorganisir - Muhammad Arief Amrullah (Fakultas Hukum Universitas Islam Indonesia, 2003)
One of the major activities of transnational criminal organizations is profit taking. Although a considerable portion of this come from drug trafficking, other forms of transnational crime may account for a significantly high percentage of all the illegal proceeds that enter the global financial system. The problem for these groups, however, is that the money derived from illicit proceeds has somehow to be made legitimate through the laundering process.